Traumatic Experiences In Okky Madasari's The Outcast (2012) - PERTIWI, ENING; , Dr. M. Thoyibi, M.S; , Dr. Phil. Dewi Candraningrum, M.Ed (2015)
The study is proposed to analyze how traumatic experiences and the effect of it reflected in The Outcast novel by Okky Madasari. It is done by determining two objectives: the first to unveil traumatic experience and the second to expain the effect of traumatic experiences by using psychoanalitic theory. This study is a qualitative study. Type of data of the study is taken from two data sources: primary and secondary. The primary data source is The Outcast novel written by Okky Madasari released in 2012. Whereas the secondary data sources are other materials take from e-book, journals, some article, book of literary and internet related to the study. They are collected through library study and analyzed by descriptive analysis.The outcome of the study shows that the novel tells about various types of traumatic experiences faced by Maryam and the effect of it. This traumatic experiences is influenced by system of personality, there are id, ego and super ego. Research finding of this section are devided into two term: Firstly, the writer find seven types of traumatic experience in The Outcast novel they are: Being left by the loved one, being accused as herectic and being bullyed, being threaten to a loved one, being relocated, natural disaster, being emotionallly abused, neglect. Secondly, the writer find eight effect of traumatic experinces in The Outcast novel, they are: Anxiety and fear, feeling sad or hopeless, insomnia or nightmare, guild, shame and self-blame, shock, denyal and disbelief, fatigue, feeling diconnected or numb, confusion, difficlty of concentration. Maryam usually dominate her ego to face her traumatic experiences. So sometimes she felt regret for something which had been done.